EUROPEAN UNION - MODEL OF GLOBAL INTEGRATION -IDENTITY THROUGH CULTURAL DIVERSITY - MATEI, Alexandru (Theoretical and Practical Research in Economic Fields; Vol 11 No 2 (2020): TPREF, Volume XI, Issue 2(22), Winter 2020, 2020)
Cultural identity at both levels - national and international - remains one of the main psychological and spiritual needs. The inability to preserve their own identity automatically and naturally leads to conflicts within a society or within societies in a particular region. There is tolerance, but not sincere acceptance by peoples on a higher stage of technological and civilization advancement, the values of the new countries that have entered or will enter the European Union. Harmonizing the different cultural systems within the European Union gives the European integration model itself a long-term perspective. This process involves knowledge and respect for cultures and awareness of the European and global interdependence phenomenon, based on the elements and specifics of cultural pluralism, excluding the imposition of a unique learning model while recognizing the importance of respect for the values of other cultures in the spirit of the cultivation of universal values, giving a greater role to international exchanges so that people can move to the European space. Understanding the implications of cultural diversity is one of the challenges of the contemporary world, being one of the main objectives of a new orientation in the globalization process.